Management Analysis of the Islamic Boarding School Education System in Enhancing Students’ Motivation and Academic Achievement at Miftahul Mubtadiin Ar-Ridlo Putri Islamic Boarding School - Anida Choirin (Prodi Ekonomi Syariah Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to describe the implementation of the pesantren education system and its contribution to enhancing the motivation and academic achievement of female students at Pesantren Putri Miftahul Mubtadiin Ar-Ridlo. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The informants consisted of the pesantren caregivers, female teachers, and selected female students through purposive sampling. The findings indicate that the integrated educational system—combining formal education, religious instruction, and character development—creates a conducive, disciplined, and religious learning environment. These factors significantly contribute to increasing students' intrinsic motivation and positively impact both academic and non-academic achievements. The study concludes that the consistent and well-directed implementation of the pesantren education system can serve as a strategic instrument in shaping students’ learning spirit and holistic achievement.